The social investment capital and the cargo volume transported by sea: A var approach for Vietnam - Nguyen Thi Thuy Hong; Hoang Thi Lich; Bui Thi Thanh Nga (Logistics, 2017)
Social investment capital is one of the factors in Vietnam's economic growth. It also has a broad impact on many manufacturing and service sectors in the national economy, including maritime transport. This article will apply a quantitative method named vector autoregression (VAR) to define the impacts of social investment capital on the quantity of cargo transported by sea. Special attention will be paid to investment from the government and foreign investors. Recommendations will be suggested to improve the current situation of shipping companies in particular, and the shipping industry in general in Vietnam.
Keywords: 650; sea transported volume; social investment capital; VAR model